Optimizing temperature & C/N ratios of newspaper and green vegetable waste for methane yield through manual optimization and response surface methodology - Nayyera Farooq (00000206292); Dr. Rabia Liaquat (USPCAS-E, NUST, Islamabad, 2020)
TH-213
Keywords: MS-ESE Thesis MS Thesis